2023
DOI: 10.1097/dad.0000000000002436
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Detect Copy Number Variation in Melanoma: Droplet Digital PCR for Quantitation of the CDKN2A Gene, a Proof-of-Concept Study

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…successfully to detect CNVs in different malignancies, including melanocytic neoplasms. 5,6,[13][14][15] In our current study, we observed an acceptable concordance between ddPCR and CMA, with MYC and MYB exhibiting concordant results in 93.2% and 85.0% of cases, respectively. Similarly, studies have reported concordance rates ranging from approximately 70%-90% between FISH and CMA.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…successfully to detect CNVs in different malignancies, including melanocytic neoplasms. 5,6,[13][14][15] In our current study, we observed an acceptable concordance between ddPCR and CMA, with MYC and MYB exhibiting concordant results in 93.2% and 85.0% of cases, respectively. Similarly, studies have reported concordance rates ranging from approximately 70%-90% between FISH and CMA.…”
Section: Discussionsupporting
confidence: 68%
“…The most widely recognized CNVs in melanoma occur on chromosomal loci 6q23 (MYB), 6p24 (RREB1), 8q24 (MYC), 9q21 (CDKN2A), 11q13 (CCND1), and 12q13 (CDK4). 2,[4][5][6][7][8]11,12 The exact pathophysiologic mechanisms by which these genetic alterations contribute to melanomagenesis are not completely understood, but their implications in the evolution of melanoma are well-established. They constitute the basis of our current advances in the field of molecular genomics in pigmented skin lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have identified copy number changes of CDK genes in tissue samples 39 41 , there is limited information on their capture from the plasma of MM patients. Thus, we decided to analyze CNVs in these genes in circulating ctDNA from MM patients and determine whether these aberrations may serve as a suitable biomarker for the noninvasive diagnosis of melanoma patients.…”
Section: Discussionmentioning
confidence: 99%